1684c Development of a postgraduate programme in workplace well being. (24th April 2018) - Hodgins, M
Abstract : Introduction: Public policy has focused recently on public sector workplaces, which account for 15% of the Irish workforce, in the form of a national workplace well-being bill. The aim of this policy initiative is to ensure that each public sector employer develops a 'healthy workplace initiative'. In order to develop healthy workplace initiatives consistent with good health promotion practice, capacity building, in the form of workforce development is required. The Healthy Workplaces Framework, a key element of both the Department of Health Strategy 2016–2019 and the Healthy Ireland agenda, contains a commitment to develop a postgraduate programme in workplace well-being, in order to address workforce development, and the process by which this has taken place is the subject of this paper. Methods: The Discipline of Health Promotion in NUI Galway offer a suite of programmes (Certificates in Health Promotion) for the 'wider workforce'; those interested in developing the skills to implement health promotion initiatives in their work setting or with particular populations. Certificates have been developed to date in Cardiovascular Health/Diabetes Prevention, Oral Health and Youth Health, comprising three modules delivered over one academic year; Core Principles of Health Promotion, the specialist knowledge appropriate to the topic or setting, and direction and support for the development of an intervention in the setting or population. This project involved liaison with NUI Galway to develop a workplace wellness specialism as part of this suite of programmes. Results: Following consultation with stakeholders, the module plan was drafted, submitted and approved. The platform 'Articulate Rise' was selected based on positive University experience and specialist materials developed. Recruitment and marketing resulted in 35 places offered and students are well advanced on the programme. Discussion: Evaluation of the programme is required and will be undertaken using University student feedback policies and processes.